2020
DOI: 10.3390/genes11091014
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Agriculture in the Dissemination of Class 1 Integrons, Antimicrobial Resistance, and Diversity of Their Gene Cassettes in Southern China

Abstract: Integrons are hot spots for acquiring gene cassettes from the environment and play a major role in the bacterial evolution and dissemination of antimicrobial resistance (AMR), thus posing a serious threat. There are currently studies on integrons and antibiotic resistance genes; however, the presence and association of integrons in different agricultural crops and their subsequent dissemination and role in AMR have not been reported previously. This study examines the abundance of integrons, their gene cassett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Gene cassettes are enormous reservoirs of genetic diversity and play a major role in the evolution of bacteria to specific conditions ( Gillings, 2014 ). Our clone library analysis of gene cassettes showed that most of the gene cassettes encoding polypeptides either had no homology in the database or had so with hypothetical proteins and were novel, which was in line with the previous studies conducted in the environmental settings of integron gene cassettes ( Elsaied et al, 2007 ; Koenig et al, 2009 ; An et al, 2018 ; Ali et al, 2020a ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Gene cassettes are enormous reservoirs of genetic diversity and play a major role in the evolution of bacteria to specific conditions ( Gillings, 2014 ). Our clone library analysis of gene cassettes showed that most of the gene cassettes encoding polypeptides either had no homology in the database or had so with hypothetical proteins and were novel, which was in line with the previous studies conducted in the environmental settings of integron gene cassettes ( Elsaied et al, 2007 ; Koenig et al, 2009 ; An et al, 2018 ; Ali et al, 2020a ).…”
Section: Discussionsupporting
confidence: 90%
“…However, according to certain studies, the effect of biochar ARGs depends on the type of biochar and manure utilized (Cui et al, 2017). The abundance of integrons and accompanying antimicrobial resistance in paddy fields in a typical agricultural ecological setting of Guangxi was substantially higher than in sugarcane fields, according to our earlier study (Ali et al, 2020a). The paddy fields have different forms of anthropogenic inputs resulting in the high abundance of integrons and their subsequent gene cassettes array.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations